2018
DOI: 10.1016/j.ymben.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering in the host Yarrowia lipolytica

Abstract: The nonconventional, oleaginous yeast, Yarrowia lipolytica is rapidly emerging as a valuable host for the production of a variety of both lipid and nonlipid chemical products. While the unique genetics of this organism pose some challenges, many new metabolic engineering tools have emerged to facilitate improved genetic manipulation in this host. This review establishes a case for Y. lipolytica as a premier metabolic engineering host based on innate metabolic capacity, emerging synthetic tools, and engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 213 publications
1
123
0
Order By: Relevance
“…Rhodosporidium and Cryptococcus are the most important yeast genus studied for intracellular lipid accumulation. However, Yarrowia lipolytica is the most studied oleaginous yeast for genetic manipulations for various biotechnological applications . This may be due to the availability of genetic information on Y. lipolytica .…”
Section: Oleaginous Microorganismsmentioning
confidence: 99%
“…Rhodosporidium and Cryptococcus are the most important yeast genus studied for intracellular lipid accumulation. However, Yarrowia lipolytica is the most studied oleaginous yeast for genetic manipulations for various biotechnological applications . This may be due to the availability of genetic information on Y. lipolytica .…”
Section: Oleaginous Microorganismsmentioning
confidence: 99%
“…A recently proposed host for polyketide production is the oleaginous yeast Yarrowia lipolytica owing to the high acetyl‐CoA and malonyl‐CoA pools implicit in this organism as an industrial workhorse for lipid and organic acid production . It was recently shown that this high flux through acyl‐CoA precursors could be diverted away from lipid production and into production of the polyketide, triacetic acid lactone .…”
Section: Microbial Hosts Considered For Heterologous Polyketide Produmentioning
confidence: 99%
“…A recently proposed host for polyketide production is the oleaginous yeast Yarrowia lipolytica owing to the high acetyl-CoA and malonyl-CoA pools implicit in this organism as an industrial workhorse for lipid and organic acid production. [54] It was recently shown that this high flux through acyl-CoA precursors could be diverted away from lipid production and into production of the polyketide, triacetic acid lactone. [55,56] While no other type III PKS-derived polyketides have yet been produced by Y. lipolytica, the extraordinarily high titer achieved in this rewired strain holds promise as an exciting starting point for expanding the reach of this organism as a type III PKSderived polyketide host.…”
Section: Yarrowia Lipolyticamentioning
confidence: 99%
“…These oleaginous microorganisms are taxonomically diverse and store lipids up to 80 % of their dry cell weight (Sitepu et al 2013;Athenaki et al 2018 ;Bellou et al 2014) . However, their industrial applicability needs to be proven and commonly genetic and molecular biology tools must be developed to transform them into modifiable production platforms (Alper and Stephanopoulos 2009;Abdel-Mawgoud et al 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…H222Δ pox1-6 accumulated citrate up to 8.1 and 1889 up to 2.0 g L -1 . Considering the published data for Y. lipolytica the yields are quite low but it can be assumed that longer cultivation duration would had yielded higher values as the citrate concentration did not stagnate during the 100 hours(Abdel-Mawgoud et al 2018) . Furthermore, for the wild type of H222Δ pox1-6 it was shown that extensive improvements of the cultivation conditions could significantly improve the yield up to 132 g L -1 citrate(Moeller et al 2010).…”
mentioning
confidence: 99%